Oral Compliacation after Bone Marrow Transplantation - R. Pink; Z. Kadlec; J. Pazdera; P. Michl; P. Tvrdý; V. Zbořil; L. Rajda; J. Vondráková; E. Faber; K. Indrák (Czech Dental Chamber, 2011)
The bone marrow transplantation is a curative method in leukemia, lymphomas, immunodeficient states and solid tumors. Graft versus host disease (GVHD) is a significant complication in patients after bone marrow transplantion, most frequently affected of intestine, liver, skin and oral mucosa. Oral mucosa damage is presented by chronic and acute form of GVHD. The acute form is presented by painful ulcers, lichenoid lesions affecting practically whole oral cavity, while the chronic GVHD is compared to autoimmune diseases such as Sjögren syndrome. GVHD is a major complication of bone marrow transplantation with risk to health a therapeutic result. The treatment is long-term and involve interdisciplinary cooperation.